Reactive Java Programming - Maglie, Andrea (Apress : Imprint: Apress, 2016)
Learn reactive programming using Java and its functional aspects, sometimes called RxJava. This book shows you how to solve "callback hell" with RxJava and shows you how to write thread-safe code without hanging onto state variables which comes in handy for cloud computing software-as-a-service issues, especially when dealing with big data processes through streaming. Reactive Java Programming includes unique coverage of reactive Android programming, growing more and more popular in mobile development with the Cloud. After reading this guide to reactive programming, you'll be able to apply it to your own big data cloud applications that use Java. In this book you'll learn how to: Use and map observables Filter and combine events Employ subjects, schedulers, and backpressure Handle reactive patterns Test your RxJava code Write your own operators Carry out reactive Android programming.